Physical methods of reducing the transmission of nosocomial infections via ultrasound and probe - Abdullah, B.J.J.; Yusof, M.Y.M.; Khoo, B.H. (1998)
Nosocomial infections are posing an increasingly serious problem in the hospital setting, With the increasing use of ultrasound in medical diagnosis, there is the potential for transmission of nosocomial infections via the ultrasound transducer and coupling gel. We evaluated the use of different membranes (three types of commercially available household cling film, condom, surgical glove and Opsite) applied over the ultrasound probe to determine if these were safe, convenient, cost effective and did not impair the performance parameters of the ultrasound probe. None of the membranes impaired the physical scanning parameters using a Multi-Purpose Tissue/Cyst Phantom. The cling film was ideal for general use in terms of cost and convenience as well as safety, For sterile use time Opsite was better overall compared to the surgical glove, though it costs significantly more. The condom and surgical glove, though safe, were not very convenient to use for scanning.